1989
DOI: 10.1093/ajcp/92.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial Cystic Lesion Related to Adenocarcinoma in the Mediastinum

Abstract: The authors report here a case of lymphoepithelial cystic lesion (LECL) of unknown origin in the mediastinum, which is closely related to a signet-ring cell adenocarcinoma. A 73-year-old man presented with a mass as revealed on a chest x-ray. During surgical operation, a solid, well-circumscribed and encapsulated 9 X 9 X 8 cm tumor was isolated from the right anterior mediastinum. This tumor had neither undergone metastasis nor invaded into the surrounding tissue and lymph nodes. Light microscopy revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…On the other hand, the lymph node itself may be the primary focus. In the latter case, malignant transformation of the ectopic epithelium in the lymph node may be responsible [ 10 , 13 15 ]. However, all of these mechanisms are hypothetical and not based on scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lymph node itself may be the primary focus. In the latter case, malignant transformation of the ectopic epithelium in the lymph node may be responsible [ 10 , 13 15 ]. However, all of these mechanisms are hypothetical and not based on scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, a LEC of unknown origin located in the mediastinum has been reported only once: Ishimaru et al [3] described a 73-year-old man suffering from general fatigue who was found to have a solid mass in the anterior mediastinum on conventional chest roent genogram and CT scan. Like our case, the cyst's wall was surrounded by lymphoid tissue with germinal centers.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion, however, was different from the current case in that it was occupied with signet-ring cell adenocarcino ma and was not connected to the trachea. Ishimaru et al [3] noted that the adenocarcinoma might have derived from the epithelial element of LEC lesion and speculated that it was either a thymic cyst derived from a remnant of the third branchial pouch or a branchial cyst derived from a remnant of the second branchial pouch that was mis placed in the anterior mediastinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Anterior mediastinal SRCC is rare and the first related case of a lymphoepithelial cystic lesion (LECL) dates back to 1989. [11] Only 2 cases of primary thymic SRCC have been since been reported. [12] Here, we report on a unique case of the anterior mediastinal SRCC.…”
Section: Introductionmentioning
confidence: 99%